Electrochemically Reduced Graphene Oxide as Screen‐printed Electrode Modifier for Fenamiphos Determination. Issue 8 (17th April 2020) - Gevaerd, A.; Watanabe, E. Y.; Fernandes, K.; Papi, M. A. P.; Banks, C. E.; Bergamini, M. F.; Marcolino‐Junior, L. H.
Abstract: In this study, electrochemically reduced graphene oxide (ERGO) was used for the preparation of a screen‐printed modified electrode and applied for the voltammetric determination of fenamiphos (FNP) in tomato samples. Graphene oxide (GO) used for sensor construction was prepared according to an improved Hummers method and characterized by XRD, TEM, and FTIR, which confirmed the nanomaterial obtention. The ERGO formation was carried out from the electrodeposition by cyclic voltammetry, at 50 mV s −1 in the potential range of 0.0 to −1.5 V, during 50 cycles. ERGO‐SPE was used in the evaluation of the voltammetric behavior of FNP. The ERGO‐SPE proposed presented excellent electrochemical performance towards FNP oxidation, promoting an enhance on the anodic peak current and a decrease of peak potential. Under optimized conditions, it was possible to construct an analytical curve, using square wave voltammetry, with a linear region of 0.25 to 25.0 μM, with calculated limits of detection and quantification of 0.067 and 0.22 μM. From this, it was possible to analyze FNP in fortified tomato samples at three concentration levels, which showed recoveries values varying between 82 and 102 %. The ERGO‐SPE device proved useful in determining FNP, where the effect of the electrodeposition of the GO promoted a significant increase in the employability of the printed electrode. Abstract :